Promoting Environmental Education for Elementary School Students Around Limestone Mining Area, Gunungkidul Regency, Indonesia - Ayu Candra Kurniati; Wahyu Endah Christiani Putri; Akhmad Zamroni; Yeni Rachmawati; Saurina Tua Sagala (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Indonesia has many environmental problems, especially those related to mining. It becomes essential to provide environmental education to the younger generation. However, the environmental education curriculum has not been explicitly found in the body of formal education in Indonesia. The study area is in Gunungkidul Regency, Indonesia where the limestone mining industry has expanded in almost all areas. The purpose of this study is to assess the environmental impacts of limestone mining activities and align the possible integration of environmental education in the study area. To gather data about the environmental impacts of limestone mining activities, a desktop study, field investigation, and interviews with local communities were conducted. Analysis of the Indonesian curriculum and interviews with elementary school teachers were conducted to align the possible integration of environmental education. The environmental impacts of limestone mining activities in the study area include air pollution, water contamination, drought, soil erosion, and road damage. We provide some suggestions for learning materials including an Introduction to environmentally friendly mining activities (Science subjects, grade 4, thematic 3), an Introduction to air pollution impacts in the mining area on human breathing (Science subjects, grade 5, thematic 2), and Introduction about mining activities impacts on the air, water, and soil (Science subjects, grade 5, thematic 8). It is recommended that teachers not only teach theory but also practice and environmental observation.